PERCEPTION AND DESCRIPTION OF THE MAIN COLOR RELATIONS IN PAINTING IN THE LANDSCAPE GENRE IN FINE ART CLASSES IN HIGHER EDUCATION INSTITUTIONS (Proceedings of International Educators Conference, 2024)
Theoretical and practical subjects are conducted in higher educational institutions to acquire the necessary knowledge from fine art subjects, and knowledge and skills are formed based on the topics given in subjects. In fine arts, drawing and painting form the composition of the main disciplines and are the main basis of every visual art and applied art. Therefore, in the science of drawing, if it is required to draw and form more, its process of shading, to finish with a sense of materiality, in the science of painting, to work with colors as the original copy of the drawn image, to form the harmony of colors with each other, and to deeply master the gamma, the main color in creating a work of colors, it is important to teach knowledge such as correct perception of chromatic and achromatic colors. Regardless of the type of fine art genres, each direction has its own requirements and laws for working with colors. When creating a picture in the landscape genre, the artist's thought and the main composition in the picture are illuminated in the work by fully understanding the main color and revealing its authenticity.